2023
DOI: 10.1111/scs.13190
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of frailty among older family caregivers

Abstract: AimThe aim of this study was to investigate the prevalence of frailty and identify the demographical and clinical factors associated with frailty among older family caregivers.MethodThe participants of this cross‐sectional study were older family caregivers (n = 125) living in Eastern Finland. Data on functional and cognitive status, depressive symptoms, nutritional status, medication, chronic diseases, stroke, and oral health were obtained. The Mini Nutritional Assessment (MNA) was used to evaluate nutritiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…The risk of malnutrition assessed using the MNA is a viable tool for monitoring changes in older adults ( Casals et al, 2015 ). Previous research has shown that the MNA score in frail or pre-frail older adults is linked to physical function and independency and has been suggested as a predictor of frailty ( Casals-Vázquez et al, 2017 ; Casals et al, 2018 ; Kiljunen et al, 2023 ). Nevertheless, this association was absent in our sample, thus, a further dietary assessment is encouraged in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The risk of malnutrition assessed using the MNA is a viable tool for monitoring changes in older adults ( Casals et al, 2015 ). Previous research has shown that the MNA score in frail or pre-frail older adults is linked to physical function and independency and has been suggested as a predictor of frailty ( Casals-Vázquez et al, 2017 ; Casals et al, 2018 ; Kiljunen et al, 2023 ). Nevertheless, this association was absent in our sample, thus, a further dietary assessment is encouraged in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, other prior studies have mainly assessed physical frailty ( Jiang et al, 2023 ), family caregivers caring for individuals with frailty ( Ding et al, 2022 ; Glomsås et al, 2022 ), and family caregivers’ frailty and associated nutritional and physical factors ( Kiljunen et al, 2023 ). Some recent evidence has also assessed the associations between socioeconomic status, frailty, and comorbidity.…”
Section: Discussionmentioning
confidence: 99%